One-stage or two-stage revision surgery for prosthetic hip joint infection – the INFORM trial: a study protocol for a randomised controlled trial. Issue 1 (December 2016) - Strange, Simon; Whitehouse, Michael; Beswick, Andrew; Board, Tim; Burston, Amanda; Burston, Ben; Carroll, Fran; Dieppe, Paul; Garfield, Kirsty; Gooberman-Hill, Rachael; Jones, Stephen; Kunutsor, Setor; et al.
Abstract Background Periprosthetic joint infection (PJI) affects approximately 1 % of patients following total hip replacement (THR) and often results in severe physical and emotional suffering. Current surgical treatment options are debridement, antibiotics and implant retention; revision THR; excision of the joint and amputation. Revision surgery can be done as either a one-stage or two-stage operation. Both types of surgery are well-established practice in the NHS and result in similar rates of re-infection, but little is known about the impact of these treatments from the patient's perspective. The main aim of this randomised controlled trial is to determine whether there is a difference in patient-reported outcome measures 18 months after randomisation for one-stage or two-stage revision surgery. Methods/Design INFORM (INFection ORthopaedic Management) is an open, two-arm, multi-centre, randomised, superiority trial. We aim to randomise 148 patients with eligible PJI of the hip from approximately seven secondary care NHS orthopaedic units from across England and Wales. Patients will be randomised via a web-based system to receive either a one-stage revision or a two-stage revision THR. Blinding is not possible due to the nature of the intervention. All patients will be followed up for 18 months. The primary outcome is the WOMAC Index, which assesses hip pain, function and stiffness, collected by questionnaire at 18 months. Secondary outcomes include the following: cost-effectiveness, complications, re-infection rates, objective hip function assessment and quality of life. A nested qualitative study will explore patients' and surgeons' experiences, including their views about trial participation and randomisation. Discussion INFORM is the first ever randomised trial to compare two widely accepted surgical interventions for the treatment of PJI: one-stage and two-stage revision THR. The results of the trial will benefit patients in the future as the main focus is on patient-reported outcomes: pain, function and wellbeing in the long term. Patients state that these outcomes are more important than those that are clinically derived (such as re-infection) and have been commonly used in previous non-randomised studies. Results from the INFORM trial will also benefit clinicians and NHS managers by enabling the comparison of these key interventions in terms of patients' complication rates, health and social resource use and their overall cost-effectiveness. Trial registration Current controlled trialsISRCTN10956306 (registered on 29 January 2015); UKCRN ID 18159.